Development of energy management as the main technique of energy efficiency of industrial enterprises - Veremeyenko, Olexander (Management and Entrepreneurship: Trends of Development, 2019)
Purpose. The paper purpose is to investigate the role of energy management in improving energy efficiency of enterprises. The main problem is the control at the managerial and operational levels in the industrial enterprises.Design/methodology/approach. Taking into account industry specifics, methodological approaches to energy efficiency management require some adaptation. The expediency of using energy efficiency benchmarking tools with the use of a facet system of classification of objects was grounded, bearing in mind the priority of realization of market and economic potentials.Findings. The level of energy efficiency of production significantly affects the competitiveness of the company, which directly affects the market share occupied in a market economy. However, given the constant increase of prices for energy resources, the influence of the level of energy efficiency on the successful activity of the company increases with each passing year, and the issue of increasing energy efficiency of production becomes of paramount importance.The scientific significance of the paper lies in the study of methods based on the main provisions of energy management. These techniques will allow to analyze and evaluate one or another model of energy efficiency management of an industrial enterprise.Research limitations/implications. The urgency of the topic under study is due to the need to increase the level of energy efficiency at industrial enterprises. The subjects of the study are energy efficiency indicators and the processes of establishing energy management principles at enterprises.Originality / value. The methods based on the main provisions of energy management have been explored. The disadvantages and advantages of the facet and hierarchical system were analyzed. The necessity of introduction of energy management system in mechanical engineering enterprises has been substantiated.The conclusion is grounded on the necessity of introducing energy management systems at the machine-building enterprises. The decision of the managerial problem lies in the consistent application of the system approach to energy management.